IMPLEMENTASI METODE WEBQUAL 4.0 TERHADAP KEPUASAN MAHASISWA PADA PENGGUNAAN SISTEM INFORMASI AKADEMIK (SIAKAD) UNIVERSITAS PRABUMULIH - Akbar, M. Ali; Fajriyah, Fajriyah; Wijaya, Khana (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
The rapid development of information and communication technology has driven increased efficiency across various sectors, including academics. The Academic Information System (SIAKAD) at Universitas Prabumulih is an integrated service for lecturers, students, and staff to support academic activities. This study aims to evaluate user satisfaction with SIAKAD using the Webqual 4.0 model, which assesses website quality based on three dimensions: usability quality, information quality, and service interaction quality, and their impact on user satisfaction. The results of this study are expected to provide a comprehensive overview of SIAKAD's strengths and weaknesses, serving as a foundation for future system improvements.Keywords: SIAKAD, User Satisfaction, Webqual 4.0 Method